An evaluation of community pharmacists’ understanding of autism spectrum disorder: a cross-sectional study in Western Australia - Knights, Emily; Sunderland, Bruce; Parsons, Richard; Ziatas, K.; Caccetta, Rima (2019)
© 2019 Royal Pharmaceutical Society Objectives: To assess the knowledge and understanding of autism spectrum disorder (ASD) by community pharmacists, across Western Australia (WA) and evaluate the extent to which they incorporate ASD friendly practices in their pharmacy. Methods: A cross-sectional study involved a postal questionnaire sent to a stratified random sample of 250 community pharmacies across WA. A score of ≥10/13 (≥76.9%) appropriate responses to selected questions was considered an indication of ‘good knowledge’ of ASD. Univariate associations between ‘good knowledge’ and variables in the questionnaire were analysed using chi-square statistics, and multivariate analysis was performed using a logistic regression model. Demographic data relating to the pharmacy were used to determine the likelihood it was ASD friendly. Key findings: Overall, 97/250 (38.8%) questionnaires were returned. There were 34/96 (35.4%) respondents classified as having ‘good knowledge’. Stigma surrounding ASD was the single best indicator of ‘good knowledge’ (P < 0.0001). None of the respondents indicated they catered specifically for ASD, and 38/97 (39.2%) reported that no changes were needed to their pharmacy to improve accessibility. There were a number of demographic features that increased the likelihood that pharmacies had the potential to be ASD friendly. Conclusions: Pharmacists overall had a basic understanding of ASD. Pharmacists who identified that stigma surrounding ASD existed in the community were more likely to achieve ‘good knowledge’. There was a reluctance to improve pharmacy accessibility to patients with ASD. Pharmacists did not appear to incorporate ASD beneficial practices into their pharmacy and pharmacy environment.